Risk Factors for Mortality in Dengue Shock Syndrome (DSS) - Catharina Suharti; Tatty E Setiati; Eric CM Van Gorp; Robert J Djokomoeljanto; Moeljono S Trastotenojo; Jos WM van der Meer van der Meer; Wil MV Dolmans (MEDIA MEDIKA INDONESIANA, 2009)
Background: Dengue shock syndrome (DSS) is the most severe form of dengue hemorrhagic fever (DHF) and has a high mortality. There are two major pathological changes in DHF determining the severity of disease, plasma leakage and bleeding. Cytokines released during the immune response to dengue virus have been thought to be mediators of the process.Methods: The study involved 50 children with DSS, of whom 13 (26%) died. We investigated which clinical signs and laboratory findings are related to mortality.Results: We found that gastrointestinal bleeding and bilateral pleural effusion were significantly more frequent in non-survivors than in survivors (p<0.02 and p=0.0006, respectively). Also, mean admission levels of thrombin-antithrombin complexes (TATc) and plasminogen activator inhibitor type 1 (PAI-1), activation markers of coagulation and fibrinolysis, respectively, were significantly higher in non-survivors (p=0.004 and p=0.0006, respectively). In regression analysis, bilateral pleural effusion and admission levels of TATc were significantly associated with mortality (p=0.007 and p=0.048, respectively).Conclusions: Our data provide evidence for a relationship of mortality with pleural effusion, a marker of plasma leakage, and coagulation activation, both characteristic pathological changes in dengue shock syndrome.Keywords: Dengue shock syndrome, mortality, risk factor.ABSTRAKFaktor risiko kematian pada demam berdarah dengue dengan sindroma syok (DSS)Latar belakang: DSS merupakan bentuk klinik yang paling berat dari demam berdarah dengue (DBD) dan mempunyai angka kematian yang tinggi. Terdapat dua kelainan patologik utama pada DBD yang menentukan beratnya penyakit, yakni kebocoran plasma dan perdarahan. Sitokine yang dilepas sewaktu terjadi respon imun virus dengue diduga merupakan mediator proses ini.Metode: Studi dilaksanakan pada 50 penderita DSS anak, dimana 13 (26%) diantaranya meninggal. Investigasi dilakukan untuk mencari temuan klinik dan laboratorik yang berhubungan dengan kematian.Hasil: Perdarahan gastrointestinal dan efusi pleura bilateral secara bermakna lebih banyak ditemukan pada penderita yang meninggal dibandingkan dengan penderita yang hidup (berturut-turut p<0,02 dan p=0,0006). Rerata kadar thrombin-antithrombin complexes (TATc) sewaktu masuk rumah sakit dan kadar plasminogen activator inhibitor type 1 (PAI-1) juga merupakan petanda aktivasi koagulasi dan fibrinolisis, secara bermakna (berturut-turut p=0,004 dan p=0,0006) lebih tinggi pada penderita yang meninggal. Pada analisis regresi didapatkan bahwa efusi pleura bilateral dan kadar TATc sewaktu masuk rumah sakit berhubungan bermakna dengan kematian (berturut-turut p=0,007 dan p=0,048).Simpulan: Data dari studi ini membuktikan adanya hubungan antara kematian dan efusi pleura bilateral (suatu petanda kebocoran plasma) dan aktivasi koagulasi dimana keduanya merupakan kelainan patologik khas untuk DSS.